1970
DOI: 10.3329/bjvm.v2i1.1926
|View full text |Cite
|
Sign up to set email alerts
|

Bacterio-pathological Studies on Salmonellosis, Colibacillosis and Pasteurellosis in Natural and Experimental Infections in Chickens

Abstract: Bacterio-pathological investigation on 1751 dead chickens during one year period from January to December 2002 at the BRAC Poultry Disease Diagnostic Centre, Gazipur showed that 39.81% (n=697) cases with seven types of different bacteriological diseases of which salmonellosis (n=385), colibacillosis (n=147) and fowl cholera (n=114) were found significantly higher rate of prevalence then staphylococcosis (n=6),  gangrenous dermatitis (n=17), necrotic enteritis (n=24) and infectious coryza (n=4). Accordingly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
42
3
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 0 publications
15
42
3
1
Order By: Relevance
“…Similar report was demonstrated by Rahman et al (2004) who reported 48.1% prevalence of Salmonella infection in summer in comparison to 23.7% in winter. Our finding supports the report of Sikder et al (2005) who recorded the highest (25.0%) prevalence of Salmonella infection in rainy season than in winter (21.9%).…”
Section: Seasonal Incidence Of Salmonella and Mg Infectionsupporting
confidence: 76%
“…Similar report was demonstrated by Rahman et al (2004) who reported 48.1% prevalence of Salmonella infection in summer in comparison to 23.7% in winter. Our finding supports the report of Sikder et al (2005) who recorded the highest (25.0%) prevalence of Salmonella infection in rainy season than in winter (21.9%).…”
Section: Seasonal Incidence Of Salmonella and Mg Infectionsupporting
confidence: 76%
“…For this reason, the current preliminary screening study was conducted to shed light on the antibiotic resistance profiles and the virulence genotyping of Salmonella serotypes isolated from broiler chickens in Egypt. Interestingly, the overall incidence level of Salmonella (17%) from broilers was close to that (21.99%) reported earlier in Bangladesh [22]. Many studies showed different prevalence rates of Salmonella isolates in broilers worldwide: in Brazil, a low rate of 2.7% was reported [23], while in China, a high rate of 52.2% was reported [3].…”
Section: Discussionmentioning
confidence: 74%
“…Commercial poultry favoring the term 'Poultry industry' plays an important role which started practically during 1980s in Bangladesh (Huque, 2001). There has been a tremendous development of this sector in the country (Rahman, 2004), but the contribution of backyard poultry has been started from the ancient period. In rural area of Bangladesh, about 80-90% household rear poultry and it is important not only as a source of income for majority of women among poor but also as the context of many social and cultural activities (Sultana, 2009).…”
Section: Introductionmentioning
confidence: 99%